Korelasi Indeks Massa Tubuh dengan Kapasitas Vital Paksa Paru - Rebecca Rumesty Lamtiar; Fansisca Siallagan (Universitas HKBP Nommensen, 2019)
Lung function consists of ventilation, diffusion, and perfusion. One of the parameters used to assess the function of lung ventilation is forced vital capacity of the lungs. One of the factors that influence a person's lung function is body mass index. Some studies suggested that person obesity had a decresing of Forced vital lung capacity (FVC)The objective of this study was to see how the correlation between the Body Mass Index and Forced Vital Capacity in students of the Faculty of Sport Sciences, Universitas Negeri Medan. This was a correlative analytic study with cross sectional design. 63 male students of the sports faculty of Universitas Negeri Medan, aged 18-23 years and did not have smoking habits were selected as samples by purposive sampling method. The Body Mass Index was measured body weight and height while the measurement of Forced Vital Capacity was carried out using a calibrated Fukudo Sangyo brand. The correlation between the Body Mass Index and the Forced Vital Capacity of Lungs was analyzed using the Pearson correlation test. The mean value of the student Body Mass Index (BMI) is 22.77 with SD + 2.59. The average value of forced vital capacity of students is 106.44% with SD + 20.25. Based on the Pearson correlation test, there is a significant positive correlation between body mass index and forced lung vital capacity of the sports science faculty(p value = 0.008) with medium correlation strength (r = 0.302). The higher the body mass index, the higher the vital capacity of the student's lung force.